1995
DOI: 10.1089/scd.1.1995.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific Monoclonal Antibodies for Intravenous Treatment of Carcinoma Patients: Immunobiologic Aspects

Abstract: Immunobiologic parameters measured during a phase I trial of intravenously (i.v.) administered bispecific monoclonal antibodies (BsmAb) in renal cell carcinoma (RCC) patients are described. The BsmAb used, BIS-1, is reactive with a pancarcinoma-associated 38 kDa transmembrane glycoprotein, EGP-2, as well with the CD3 complex. Patients received during a 2 h i.v. infusion F(ab')2 fragments of BIS-1 at doses of 1, 3, or 5 micrograms/kg body weight during concomitantly applied subcutaneous (s.c.) IL-2 treatment. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Administration of an EpCAM/CD3-bispecifi c BITE antibody to mice resulted in a transient increase in serum levels of TNF and IFN [17]. Another bispecifi c anti-CD3 antibody also caused a rapid increase in plasma levels of TNF and IFN in carcinoma patients [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of an EpCAM/CD3-bispecifi c BITE antibody to mice resulted in a transient increase in serum levels of TNF and IFN [17]. Another bispecifi c anti-CD3 antibody also caused a rapid increase in plasma levels of TNF and IFN in carcinoma patients [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…A further study also showed that administration of a monospecific anti-CD3 antibody to patients after renal transplantation resulted in decreases in lymphocyte counts [20]. Administration of the bispecifi c antibody BIS-1 (anti-CD3 x anti-EGP-2) to renal cell carcinoma patients caused a rapid decrease in circulating mononuclear cells in the peripheral blood [18,19]. The effect was dose-dependent and there was a preferential decrease in LFA-1+CD3+/CD8+ lymphocytes [18].…”
Section: Discussionmentioning
confidence: 99%
“…The accessibility of an Ag in organs can be influenced by differences in vasculature between organs or by differences in FcRn affinity of the mAb, which results in differences in transcellular transport subsequently leading to either more or less Ab being available for the target Ag (25,29). The Ag density per organ or the presence of the basal lamina, which has been suggested to shield the epithelial cells from the circulation in humans (3,30), can influence the tissue localization of the mAb as well.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Because most TAAs that are targeted are also expressed on some normal cells, unwanted side effects may occur, particularly when the bsAb reagents are applied systemically. 35,36 There are several advantages to the decision to bind a bsAb first to a tumor vaccine for local application and to the choice of the foreign viral HN molecule, which is easily introduced ex vivo into human tumor cells, as a tumor target: (a) the HN is not expressed on any normal cells of the cancer patient, (b) targeting the bsAb to HN does not interfere with the tumors' TAA expression and presentation, and (c) a common anchoring molecule avoids the need to produce bsAb separately for every type of cancer. The specificity controls revealed that the bsAb did not bind to nonvirusmodified tumor cells and that the parental mAbs could not increase vaccine immunogenicity.…”
Section: Discussionmentioning
confidence: 99%